(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Recognition, learning, and work increasingly transcend borders. People, experiences, and data move globally for education, employment, migration, and personal growth. Yet credentialing standards, digital wallets, and verification platforms, while rapidly evolving, remain fragmented, siloed within local boundaries, and unevenly adopted. This makes inclusive, equitable, and portable skills recognition difficult for individuals. A lack of awareness of available and emerging standards and the benefits of their adoption is a significant barrier to cross-border recognition. Challenges include inflexible legacy systems, a lack of awareness and alignment, fragmented infrastructure, and limited funding for end-to-end ecosystem testing, particularly across diverse contexts and borders. Artificial Intelligence (AI) promises opportunities and complexities, with capabilities such as automated skill extraction and fraud detection, but also risks, including bias and privacy concerns. As credentialing systems gain momentum, the diversity of standards and technical solutions will serve to empower open recognition or further fragment it. The Paris Declaration on Open Recognition principles—openness, decentralization, empowerment, and systemic adoption—provide a framework for realizing these goals. As global mobility, remote work, and digital learning become the norm, we need a living map of digital credentialing standards and solutions to understand how recognition systems interact (or don’t), highlighting alignment, fragmentation, and opportunity, enabling transitions from isolated efforts to coordinated, open, and inclusive recognition across borders. This allows policymakers, technologists, educators, and employers to see which standards, platforms, and practices can converge or interoperate and surfaces the differing data formats, incompatible standards, or a lack of trust frameworks. It spotlights promising practices, regional hubs of innovation, and pathways to mutual recognition agreements. An international map also supports both scale (adoption across geographies) and sustainability (resilience over time) and empowers people and organizations about where to invest, how to collaborate, and what to advocate for, whether it’s shared infrastructure, policy change, or ethical standards. Ultimately, it strengthens the global open recognition movement. Clinic Rationale This clinic identified the international landscape of digital credentialing for open recognition, enabling transition from isolated efforts to coordinated, open, and inclusive recognition across borders. Clinic Experience Using the Paris Declaration on Open Recognition principles, participants co-created a living map of digital credentialing for open recognition across borders. They engaged in a hands-on, collaborative session to crowdsource an open and shared understanding of current credentialing standards and technical solutions across regions and continents. Using maps and group discussion, participants mapped their local and international experiences with credentialing technologies. Clinic Goals Identified region-specific digital credentialing and open recognition initiatives. Mapped key frameworks and standards across regions. Documented various technical infrastructure and solutions. Built shared understanding of commonalities, differences, and gaps. Created a foundational living artifact, a digital international map to inform future collaboration and alignment. Clinic Deliverables From the clinic insights, we will produce and publish a public interactive Digital Credentials for the Open Recognition landscape map. Keywords: open recognition, open badges, digital credentialing, cross-border portability, interoperability standards.